1996
DOI: 10.1177/144078339603200205
|View full text |Cite
|
Sign up to set email alerts
|

The social bases of environmentalism in Australia

Abstract: Interpretations of social and political movements as reflecting social cleavages, especially 'class bases', have formed the backbone of political sociology. Ac cordingly, Western environmental movements are often explained in terms of their alleged class and generational bases. This research assesses social base explanations of support for environmental new politics in Australia. Using nationally representative survey data, it examines the impact of (new) class, status, generation/cohort, and other aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…In Australia environmentalists tend to be employed in professional occupations and to be politically left o f centre, but are less likely to be aligned with a religious denomination (Tranter, 1996). Such findings are consistent with Inglehart's (1997, page 142) and Kriesi's (1989) views that new social movements are underpinned by a 'new class' o f highly educated technocrats.…”
Section: Social and Political Background Of Environmental Issue Supportsupporting
confidence: 77%
“…In Australia environmentalists tend to be employed in professional occupations and to be politically left o f centre, but are less likely to be aligned with a religious denomination (Tranter, 1996). Such findings are consistent with Inglehart's (1997, page 142) and Kriesi's (1989) views that new social movements are underpinned by a 'new class' o f highly educated technocrats.…”
Section: Social and Political Background Of Environmental Issue Supportsupporting
confidence: 77%
“…Whilst it has typically been found to be highest amongst the NMC, it has also been 109 CLASS THEORIES OF ENVIRONMENTALISM 124ep05.qxd 10/11/03 08:07 Page 109 relatively high across a range of occupational and 'class' categories [Van Liere and Dunlap, 1980;Australian Electoral Study, 1990;Papadakis, 1993;Tranter, 1996]. And there is some evidence from the 1980s onwards of a dilution of NMC dominance [Dalton, 1988Tranter, 1996;Tranter and Pakulski, 1998].…”
Section: Environmental Politicsmentioning
confidence: 96%
“…Kriesi [1989] found that whilst NSM (including ecological and antinuclear) mobilisation potential was particular high, in the Netherlands, amongst the social-cultural occupational sector of the NMC, it was next highest amongst skilled industrial workers (a core trade union constituency), followed by lower-level employees and administrative and commercial workers, and higher amongst these categories than all other class and occupational categories. Recent work from Australia [McAllister et al, 1990;Papadakis, 1993;Tranter, 1996] finds that support for environmentalist positions is generally (albeit unevenly) high across socioeconomic strata, and that disparities between strata appeared to be diminishing during the 1980s and 1990s. The same studies found the industrial working class to be under-represented amongst active participants in the environmental movement, but in view of the findings on working class attitudes the explanation for this would seem to lie elsewhere than in notions of general working class hostility to environmentalism.…”
Section: The Industrial Working Class and Environmentalismmentioning
confidence: 96%
See 2 more Smart Citations